The Jehovah’s Witness obstetric patient – a literature review - Rajewska, Aleksandra; Mikołajek-Bedner, Wioletta; Sokołowska, Małgorzata; Lebdowicz, Joanna; Kwiatkowski, Sebastian; Torbè, Andrzej (Anestezjologia Intensywna Terapia, 2019)
The patient’s right to refuse blood transfusion must be honoured in case of its clear expression. Some special pharmacologic and/or surgical procedures can be useful in a Jehovah Witness (JW) parturient. In case of excess blood loss the maintenance of peripheral tissue oxygenation is crucial. Only a few hospitals have equipment for blood salvage, and alternative oxygen carriers have potentially lethal side effects. Findings suggest that obstetric facilities should develop special algorithms of management in the case of the JW obstetric patient, with written declaration of which elements of blood are not acceptable for the patient, early diagnosis and intensive treatment of anaemia in pregnancy, administration of antifibrinolytic agents before surgery, use of electric surgical tools to restore haemostasis, early detection and aggressive treatment of excessive blood loss and, last but not least, close cooperation between obstetricians and anaesthesiologists, including sharing the information about the patient’s refusal of blood transfusion.